USING SENTINEL-2 DATA FOR ABOVE-GROUND MANGROVE BIOMASS AND CARBON STOCKS MAPPING OVER 7 YEARS (2016-2022) IN TIEN YEN, QUANG NINH PROVINCE - Tri Son, Ha; Duy Quang, Pham; Hai Hoa, Nguyen; Van Truong, Vu (Journal of Forestry Science and Technology, 2023)
Mangrove forests are found along tropical and subtropical coastlines. They have vital functions in preventing coastal erosion, mitigating effects of wave actions, and protecting coastal habitats. This study used the Sentinel-2-derived CMRI thresholds for coastal land covers (CMRI > 0.47 for mangrove forests, -0.25 < CMRI ≤ 0.47 for non-mangrove forests, and CMRI ≤ -0.25 for water bodies). The CMRI is suitable for detecting mangrove cover along the coast of Tien Yen district with overall accuracy over 90.5% and Kappa coefficient greater than 0.85 for the whole selected years. Overall, the extent of coastal mangrove forests along the coast of Tien Yen, Quang Ninh province increased by 792.7 ha in 2022 compared to 2016. Moreover, the total AGB and AGC of mangrove forests were estimated at 2,761,533 tons and 1,311,728 tons in 2022, respectively. The total CO2 sequestration was estimated at 4,814,042 tons in 2022, an increase of 1,212,632 tons compared to 2016. The study assumed the constant carbon price of US5 ton-1 CO2, US11 ton-1 CO2, and US15 ton-1 CO2, the total amount of CO2 paid for Tien Yen district would be about US6,063,160, US13,338,952, and US18,189,480, respectively. The study highly suggests that mangrove blue carbon should be adopted and implemented toward sustainable mangrove management in Tien Yen district, including mangrove PES schemes. However, some key factors should be clearly addressed to ensure the success of mangrove blue carbon option in Tien Yen district, including an increased awareness of the value of mangrove ecosystem promoted; the involvement of local communities encouraged; other issues in relation to PES policy revised.